On modernity and the other in Leanne Simpson's work, Islands of Decolonial Love - Falcao, Maria de Fatima Lopes Vieira; Silva, Gislane Goncalves; Galvao, Naiana Siqueira; Silva, Cicero da [UNESP] (Univ Serena, Fac Humanidades, 2021)
This work aims to give a brief account of modernity and the other in the work Islands of Decolonial Love, by the writer Leanne Simpson. The writer has a persuasive indigenous voice that has attracted the attention of many readers across Canada's borders on land and indigenous issues, extractivism, and the environment. In the focused work, the author brings the non-indigenous reader closer to the construction of indigenous knowledge by presenting a material that goes beyond the written word. The nation which Leanne Simpson belongs to and so many other indigenous peoples have suffered and still suffer from the marks of colonization. To think about the narratives and conversations of the characters in the Islands of Decolonial Love is to reflect in the reader the invisible 'cracks' that the civilizing process and its 'obscure' side unleash under the 'ethics' of the rhetoric of modernity and the progressive discourse of capitalism. One cannot deny the existence of the other.
Keywords: modernity; coloniality; indigenous; pressure; the other